Pengaruh Era Digital Terhadap Perkembangan Bahasa Anak - Puji Rahayu (Institut Agama Islam Negeri Metro, 2019)
Language development is an indicator of development. 80% of developmental disorders are caused by lack of stimulation. Use of interactive media (digital) is one of the stimulations in this digital era. Interactive media is an audio-visual media that is expected to improve children's language skills. This media can increase vocabulary, phonation and the child's ability to understand colors, numbers and discourse / text.